Serum anti-mullerian hormone levels and age among Samoan women - Grace O’Brien; Geralyn Lambert-Messerlian; Nicola L. Hawley; Ulai T. Fidow; Take Naseri; Muagututi‘a Sefuiva Reupena; Erin E. Kershaw; Marinelle B. Azar; Martha M. Pangburn; Stephen T. McGarvey (Reproductive Biology and Endocrinology)
Abstract Background Serum AMH levels in adult women are part of the diagnostic criteria for polycystic ovary syndrome (PCOS), a condition with marked infertility and metabolic risks. Yet, little is known about AMH levels among women from ethnic minority populations, especially its associations with age and obesity. The objective is to describe the association of age and serum anti-mullerian hormone (AMH) among Samoan women, provide age specific AMH reference levels, and examine the associations of AMH with adiposity and reproductive factors. Methods A cross-sectional, retrospective study of a representative community-based sample from Samoa was conducted. 670 women with no known reproductive disorders, reproductive surgeries, or hormonal contraceptive use, age 25–51 years, were included. Adiposity was assessed by body mass index (BMI) using Polynesian-specific criteria for obesity. Serum AMH was determined by enzyme-linked immunosorbent assay. Serum total testosterone and sex hormone binding globulin were measured, and the free androgen index was calculated. Hormonal contraceptive use, menstrual regularity, and tobacco use were assessed by questionnaire. PCOS prevalence was estimated using current guidelines. Results Despite a high prevalence of obesity and overweight in Samoan women, serum AMH and its age related decline were similar to those reported in other populations. AMH was negatively associated with age. AMH decline with age in Samoan women is best described by a cubic model. AMH was not associated with BMI or insulin resistance. PCOS prevalence was estimated at 3.4–5.1%. Conclusion This study was the first to construct an age specific AMH reference range for Samoan women. PCOS prevalence appears low, supporting other published studies that have demonstrated a complex relationship between adiposity and reproductive health in Samoan women. Clinical trial number Not applicable.